Influence of oat and spring pea mixtures on forage characteristics in different environments. (31st March 2020) - Pflueger, Nathan P.; Redfearn, Daren D.; Volesky, Jerry D.; Bolze, Ron; Stephenson, Mitchell B.
Abstract: Forage mixtures including oat ( Avena sativa L.) and spring pea ( Pisum sativum L. spp. sativum ) provide opportunities to optimize forage production with increasing forage quality, relative to single species stands. Under different climate scenarios, adjusting seeding rates of these mixtures may produce variable results in forage quantity and quality. We conducted a 2‐yr study at three study sites to evaluate forage characteristics within mixtures of oat and spring pea stands across a semi‐arid to subhumid precipitation gradient. At the western‐most and driest location (219 mm March–June precipitation), the oat monoculture produced 16−19% more total biomass than seeding treatments with mixtures of oat and spring pea. In contrast, at the moderate‐precipitation site (255 mm precipitation), no differences in total biomass were detected for the oat monoculture and seed mixtures of oat and spring pea. Large variation at the wettest site (339 mm precipitation) limited our ability to detect differences for total biomass production across treatments, but weed pressure in Year 2 of the study reduced forage production. Typically, crude protein (CP) concentration decreased linearly ( P < .01) as spring pea decreased in the seeding rate, but CP concentration and total CP yield varied for the seeding rate treatments at the different study sites. Environmental condition may influence the benefit of substituting spring pea into a properly managed oat forage crop to increase forage quality. The contribution of spring pea forage in the total forage biomass of mixtures may be limited, especially in drier conditions.